(untitled) (Biodiversitas Journal of Biological Diversity, 2014)
Sunarto, Tsaaqifah H, Purwoko C, Pangastuti A. 2014. The diversity of non-methanogenic bacteria involved in biogas production from tofu-processing wastewater. Biodiversitas 16: 62-68. The energy crisis is an important current issue, so diversification of energy is needed to solve the problem. Biogas from tofu-processing wastewater is one potential alternative energy to be developed because it has high organic matter content. The amount of methane formed by methanogens is also influenced by the presence of bacteria, so it is necessary to do research on the diversity of non-methanogenic bacterial communities. This study aimed to determine the diversity of non-methanogenic bacteria in anaerobic fermentation using ARDRA (Amplified Ribosomal DNA Restriction Analysis) method. Tofu-processing wastewater was anaerobically fermented, followed by DNA extraction, amplification of 16S rRNA marker gene, and cloning. Then, restriction was done using MspI and AluI restriction enzymes, followed by sequencing of different patterns. The data were analyzed to know the diversity of non-methanogenic bacteria and the relative importance of each phylotype in the community using Shannon-Wiener index of diversity (H’) and evenness (E).The results showed that there were 38 positive clones of 16S rRNA genes clones. The sequencing using BLASTn analysis showed the presence of 10 species of non-methanogenic bacteria. There were four sequences with 97% similarity, indicating that the bacteria belong to species from GeneBank data. There were 6 sequences that had 96% similarity with the closest relative in the database, indicating that these bacteria are new species. The Shanon- Wiener index was 1.291, categorized as low and the evenness was 0.561, categorized as low because there was dominance of a species.